REVIEW OF OXIDATIVE STRESS AND ANTIOXIDATIVE - BERAKDAR, NOURA; ALAHMAD, AYA (Innovare Journal of Life Sciences, 2022)
Oxidative stress is one of the causative factors of many diseases. According to the pathophysiology, monocytes, macrophages, and normal white cells are produced in large quantities that produce reactive oxygen species (ROS) as well as cytokines that can stimulate cell and tissue damage. Oxidative stress occurs when there is an imbalance between free radicals and antioxidants within the body. ROS (free radicals) are produced by normal cellular metabolism and interact with biomolecules such as protein, lipids, and DNA to cause cellular damage and are responsible for degenerative changes. These processes are responsible for causing many diseases such as cardiovascular diseases. The agents responsible for this damage are reactive oxygen and nitrogen species resulting from various processes that destroy intracellular components such as nucleic acids, proteins, and lipids. These agents can lead to necrotic cell death or apoptosis by activating specific intracellular signaling pathways.